EPIDEMIOLOGI PSIKOSOSIAL DAN DETERMINAN SOSIAL DI LAYANAN RUJUKAN: TINJAUAN LITERATUR PENGEMBANGAN MODEL MANAJEMEN STRES TENAGA KESEHATAN MELALUI PENDEKATAN TEORI TRANSAKSIONAL DI RSUD PROVINSI NTB - Anna Indriani; Yuly Peristiowati (Bajang Institute, 2026)
Background: Healthcare workers in referral hospitals are frequently exposed to chronic occupational stress due to high workloads and service complexity. Objective: This study aims to develop a stress management model for healthcare workers through a Transactional Theory approach, considering psychosocial epidemiology and social determinants at RSUD Provinsi NTB. Methods: This research employed a Systematic Literature Review (SLR) method, searching literature across Scopus and Google Scholar databases within the 2014–2024 period. Inclusion criteria focused on studies integrating coping mechanisms, social determinants, and referral services. Results: Key findings indicate that occupational stress in referral services is triggered by an imbalance between job demands and job control. From a Transactional Theory perspective, the effectiveness of stress management significantly depends on the staff's secondary appraisal of organizational support. The proposed model emphasizes three intervention levels: modifying social determinants (structural), strengthening cognitive capacity (individual), and providing social support systems (interpersonal). Conclusion: Integrating psychosocial epidemiology into the management policies of RSUD Provinsi NTB is crucial for creating a supportive work environment and sustainably improving the quality of patient care.